2014
DOI: 10.1017/jgc.2013.30
|View full text |Cite
|
Sign up to set email alerts
|

The Grief Grapevine: Facebook Memorial Pages and Adolescent Bereavement

Abstract: How adolescents use the social networking site Facebook to express grief is a growing area of research. In reviewing current literature, it is evident that many questions still remain unanswered. Additionally, this ever-evolving platform for grief, mourning and bereavement may hold many implications for educators, policy developers and school counsellors and how they manage and support adolescents dealing with the sudden death of a peer. This article explores the reasons why Facebook memorials may appeal to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
2
9
0
2
Order By: Relevance
“…As previously discussed, because SNSs offer a place to rapidly connect with other mourners, create and share tributes, give or receive social support, or simply observe others' griefwork, they have become popular locations to memorialize deceased celebrities (e.g., Radford & Bloch, 2013;Sanderson & Cheong, 2010) as well as personal friends and family members (Carroll & Landry, 2010;DeGroot, 2012;Frost, 2014;Kern et al, 2013). In the same vein, SNSs also provide a convenient and relatively public platform for individuals to channel their grief into proactive efforts to advance social causes endorsed by the celebrity or in honor of the celebrity, such as donating to charities (e.g., Brown, 2010), or in the case of the current study, educating others with health-related information or directives such as suicide prevention advice (e.g., Krysinska & Andriessen, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously discussed, because SNSs offer a place to rapidly connect with other mourners, create and share tributes, give or receive social support, or simply observe others' griefwork, they have become popular locations to memorialize deceased celebrities (e.g., Radford & Bloch, 2013;Sanderson & Cheong, 2010) as well as personal friends and family members (Carroll & Landry, 2010;DeGroot, 2012;Frost, 2014;Kern et al, 2013). In the same vein, SNSs also provide a convenient and relatively public platform for individuals to channel their grief into proactive efforts to advance social causes endorsed by the celebrity or in honor of the celebrity, such as donating to charities (e.g., Brown, 2010), or in the case of the current study, educating others with health-related information or directives such as suicide prevention advice (e.g., Krysinska & Andriessen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…SNSs such as Twitter and Facebook have made a variety of mourning rituals more accessible to people grieving personal friends and loved ones as well as those grieving public figures. These platforms give users the opportunity to pay respects and express their grief, to give and provide social support by interacting with others who are bereaved, or to simply reduce loneliness by observing others' grief and feeling a part of a larger community of mourners (Carroll & Landry, 2010;DeGroot, 2012;Frost, 2014;Kern, Forman, & Gil-Egui, 2013). Studies have found that following Michael Jackson's death, grieving fans used Twitter to memorialize the late pop star, and to share information and emotional support with others (Lee & Goh, 2013;Sanderson & Cheong, 2010).…”
Section: Rituals Of Mourning For Celebritiesmentioning
confidence: 99%
“…Moreover, though less often, the creation of "pages" and "group" dedicated to the memory of the deceased is observed on Facebook, giving users the opportunity to join the community at the touch of a button -"Like" in the first case and "Join" in second-. This allows users to participate in a web community that will mourn, memorize and share narratives about the dead (Frost, 2014). There are, consequently, two different types of pages for people who have died; the pages dedicated to a dead's memory that can be joined by anyone as long as he/she becomes a member and the profiles of the deceased members of the Facebook community.…”
Section: Nd International Conference On Cultural Informatics Communimentioning
confidence: 99%
“…However, digital immortality has moved beyond simple memorial pages (Frost 2014), and as early as 1997 the term thanatechnology was instituted by Sofka (1997) to represent this desire to preserves one's soul and assets digitally after death; it has since been developed further by Sofka, and Gilbert (2012). There have also been cases where people have received 'beyond the grave' updates, either from dead friends (McAlear, 2011), or companies dedicated to creating digitally immortal personas (LivesOn, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%